Peroxiredoxin 5 Acts as a Negative Regulator of the Sodium-Chloride Cotransporter Involved in Alleviating Angiotensin II-Induced Hypertension - Hoon-In Choi; In Ae Jung; Soo Wan Kim (Antioxidants)
Chronic kidney disease (CKD) and hypertension are interconnected, worsening each other. Recent studies have shown that the reduction of peroxiredoxin 5 (Prdx5) accelerates kidney fibrosis, a hallmark of CKD. This study aims to observe whether the deficiency of Prdx5 also contributes to the worsening of CKD-related hypertension. Angiotensin II (Ang II, 1000 ng/kg/day) was infused into Prdx5 wild-type (WT) and Prdx5 knock out (KO) mice (each group; n = 6). The blood pressure was higher in the Ang-II-infused Prdx5 KO mice than in the WT mice. Ang-II-induced ROS/RNS generation and fibrotic marker expressions were also higher in the Prdx5 KO mice. In particular, the expression of the sodium-chloride cotransporter (NCC), an ion transport protein important for sodium retention in the distal convoluted tubule, and the NCC’s phosphorylation at Thr53 were increased in the kidney of Ang-II-infused Prdx5 KO. The activity of an WNK4-SPAK/OSR1, upstream activator of the NCC, was also increased. In 209/mDCT cells, the knockdown of Prdx5 (siPrdx5) increased the activity of Ang-II-mediated WNK4-SPAK/OSR1-NCC signaling and Ang-II-mediated ROS generation, whereas Prdx5 overexpression showed opposite results. In conclusion, Prdx5 negatively regulates the WNK4-SPAK/OSR1-NCC signaling axis, indicating its potential as a candidate for antihypertensive drug development through NCC regulation.